The impact of foreign direct investments on the economic growth rate and domestic investments of Malaysia / Yong Sze Wei, Chong Vui Hok and Gan Siew Ling - Yong, Sze Wei; Chong, Vui Hok; Gan, Siew Ling (Research Management Institute (RMI), 2012)
Malaysia was among the countries in Southeast Asia which experienced rapid economic growth since the 1970s. In fact, during the period, Malaysia underwent significant economic transformation, from an agricultural-based to a manufacturing and service-based economy. Although her growth was somewhat derailed by the Asian Financial Crisis in 1998 - 1999, Malaysia had since recovered. The recovery was seen to be in no small part due to the contribution from foreign and domestic investments. In particular, foreign direct investments (FDIs) had been viewed as an engine of economic growth in Malaysia through its spillover effects such as capital injection, technology transfer and creation of job opportunities. In spite of the perceived beneficial impacts of FDIs, the government targetted to reduce Malaysia's dependence on FDIs and to raise the proportion of domestic private investments (DPIs) to 60% of total investments by 2020. Therefore, does the inflow of FDIs in Malaysia crowd out domestic investment or complement it? Due to that, the main objective of the study is to investigate the relationship and effect of domestic investment in boosting the Malaysia economic growth as compared with foreign direct investment in this globalization era. The time series data from the period of 1970 until 2009 will be adopted in order to capture the different implications of the domestic and foreign investment towards Malaysia economic growth particularly prior and post crisis. Methods that applied in this study consist of Unit Root Test, Cointegration Test, Granger Causality Test based on Error Correction Model and Impulse Response function. Major contribution of this study is to provide essential insights to the policymaker in strategizing the appropriate policies to the allocation of aggregate investment for the country